Ho'onani : hula warrior - Gale, Heather (Children's author) (Tundra Books, 2019)
"An empowering celebration of identity, acceptance and Hawaiian culture based on the true story of a young girl in Hawai'i who dreams of leading the boys-only hula troupe at her school. Ho'onani feels in-between. She doesn't see herself as wahine (girl) OR kane (boy). She's happy to be in the middle. But not everyone sees it that way. When Ho'onani finds out that there will be a school performance of a traditional kane hula chant, she wants to be part of it. But can a girl really lead the all-male troupe? Ho'onani has to try..."--